Information sources and adoption of vaccine during pandemics. Issue 4 (28th October 2014) - Sengupta, Sanjit; Deanna Wang, Hui-ming
Abstract : Purpose: – The purpose of this paper is to investigate the effects of different information sources on consumer health behavior during pandemics. Design/methodology/approach: – We collected survey data from 321 adults in a large western US city during November 2009 by mall and street intercepts. We analyzed their beliefs, attitudes and intentions with regard to adoption of the H1N1 (swine flu) vaccine. We developed and tested two alternative models on the role of mass media and personal information sources on the attitude towards the disease and the intention to get vaccinated. Findings: – Our study finds that mass media and personal sources of information simultaneously impact perceived threat from disease (attitude) and the intention to get vaccinated during a global pandemic. Personal information sources are more effective than mass media sources in impacting both attitude and intention. While the impact of mass media weakens from the attitude stage to the intention stage, the impact of personal information sources increases from the attitude stage to the intention stage. Originality/value: – The contribution of this paper to health policy makers and marketers is to draw implications on how mass media and personal information sources could be better utilized to counter future global pandemics.